The Main Problems of Universal Typological Classification of Documents - Masiokas, Mykolas (Knygotyra, 1985)
The author considers the collection of documents from the stand of Marxist dialectics as an objective social phenomenon. The collection of documents has been formed on the base of typical social inquiries. For the regulation and usage of the collection of documents it is necessary a universal typological classification which includes written, phonetical, graphic and matrix documents. Such a classification in the limits of informaties can be created on the basis of common theory of collection of documents.The paper carries factographic scheme which develops and creates the document on which the formation of typological classification signs are based.Separate scientific disciplines have worked out some particular typological classifications (publishing, bibliographic, library, book commercial, archives, etc) interpoling which it is possible to raise a new, universal one. The article represents such a variant. All the general collection of documents in it is divided into ten functional types. Three main are: scientific, artistic, publicistic, five supplementary (administrative, industrial, scientific-popular, educational and inquiry) two special types (documental monuments and bibliographical documents).